Relação da eficiência relativa dos gastos com assistência social com os indicadores sociais das capitais brasileiras no contexto da pandemia da Covid-19 - Steindorfer, Igor Barroso (2024)
Understanding the concept of governance, under the pillar of social responsibility, with a focus on promoting social justice, gives rise to the need for ongoing evaluation of public social assistance policy. Regarding the constitutional principle of efficiency applied to public spending, this study aimed to analyze the relationships between the relative efficiency of spending resources from the National Social Assistance Fund (FNAS) and the social indicators of Brazilian capitals. To this end, this documentary, descriptive, and quantitative research used Data Envelopment Analysis (DEA), with stacked data, for the years 2019 to 2022, considering the model with variable returns to scale oriented to outputs (BCC-O). In addition, regression tests and tests of means per period, by geographic region, were also used. The main findings of the results indicate that the efficiency of the expenditure analyzed had a strong negative and significant influence on the Infant Mortality Rate (IMR) of Brazilian capitals and that in highly populated capitals such as São Paulo, the number of inhabitants has a significant positive influence on the efficiency of the expenditure examined. As for the main findings of the other tests, it is also possible to highlight that, in 2022, after the pandemic, four capitals reached the efficiency frontier, with this period (post-pandemic) being different and significant among those observed. From a practical point of view, the results of this study support better decisions, whether they are adopted by public managers who define public policies, by managers responsible for defining the allocation of resources, or even by municipal managers responsible for the budgetary execution of resources that serve the most vulnerable minorities.